Safety Management in Public Building Construction: A Case Study of Pokhara Valley - Giri, Om Prakash; Poudel, Kamal; Shrestha, Santosh Kumar (Journal of Business and Management, 2023)
Background: Construction site safety is a major issue in the construction industry all around the world. In a developing country like Nepal, the number of construction industries is growing haphazardly at a high rate but they are not being able to cope with factors associated with construction site safety. Objective: The main objective of the study is to explore the status of safety management in public building construction projects and to suggest measures for improvement. Methodology: To achieve the objective of the study, data were collected from the Engineers and site management personnel through a questionnaire survey. Data were analyzed descriptively by IBM SPSS and presented in tables and diagrams. Conclusion: The identified major safety issues for public building construction sites are lack of regular safety inspection, lack of use of personal protective equipment (PPE), lack of conducting safety training, and a lack of proper safety policy and plan including a lack of an adequate budget for safety management. Increased worker safety awareness and introducing safe working practices through training and induction programs are vital to reducing construction site safety. The outcome of the study will be helpful while formulating a project-based construction site safety policy.